Mursnowwhite / Nur Sakinah Abdullah - Abdullah, Nur Sakinah (2021)
The Mursnowwhite shop is a shop that sells biscuit that is the famous, delicious and affordable price. Basically, this shop only provides for bakery purposes. The product of this biscuit actually would be a good choice for many events which is the Raya event and birthday event and it also can be a better gift to buy for anyone who deserves it. This shop is only opened as an online business for customers who want to purchase it especially to our targeted customers are from many kinds of buyers category obviously. This business is serving on April 2021. And, everything is good with the online business situation because online shop like this was easier for people to recognize the shop and they are just waiting for their orders to have arrived. Also, if any of near area the shop will offer the cash on delivery as the special services for any customers that close to our shop location. The Mursnowwhite is a simple shop or bakery because it just sells only one flavor or type of biscuit which is makmur biscuits with milk flavor. The biscuits are provided for two types of price which make the customers can choose to buy one of the two prices. Not just that, with the quantity of the biscuits, actually are good strategies to attract customers that maybe can be known at overseas too.